2018
DOI: 10.1177/0363546517751397
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Platelet-Rich Plasma and Platelet-Rich Fibrin in Arthroscopic Rotator Cuff Repair: A Meta-analysis of Randomized Controlled Trials

Abstract: The current evidence indicates that the use of PRP in rotator cuff repair results in improved healing rates, pain levels, and functional outcomes. In contrast, PRF has been shown to have no benefit in improving tendon healing rates or functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 56 publications
5
127
1
10
Order By: Relevance
“…En tendinopatías aquileas, se recomienda el PRP como una terapia de segunda línea, ya que se ha reportado que no existen diferencias significativas entre su uso y el agua salina. 17,20 Por otra parte, en las tendinopatías patelares, no se han desarrollado estudios controlados aleatorizados que concluyan sobre el uso de PRP vs terapias conservadoras, por lo que este podría ser utilizado en casos resistentes a la terapia conservadora. 17 Otros autores 19 mencionan que el uso del PRP mejora la regeneración, disminuye el dolor y ayuda en la capacidad funcional del hombro en personas con desgarros del manguito rotador.…”
Section: )unclassified
“…En tendinopatías aquileas, se recomienda el PRP como una terapia de segunda línea, ya que se ha reportado que no existen diferencias significativas entre su uso y el agua salina. 17,20 Por otra parte, en las tendinopatías patelares, no se han desarrollado estudios controlados aleatorizados que concluyan sobre el uso de PRP vs terapias conservadoras, por lo que este podría ser utilizado en casos resistentes a la terapia conservadora. 17 Otros autores 19 mencionan que el uso del PRP mejora la regeneración, disminuye el dolor y ayuda en la capacidad funcional del hombro en personas con desgarros del manguito rotador.…”
Section: )unclassified
“…Some studies involving the systematic comparative analyses of such studies concluded that PRP is effective in reducing/eliminating pain [94][95][96][97]. However, other similar studies concluded that, although the evidence is strong, the statistical evidence is not sufficient to support the hypothesis [98][99][100][101].…”
Section: Physiological Source Of Pro-and Anti-inflammatory Cytokines mentioning
confidence: 99%
“…PRP is the most commonly tested, undefined biological adjuvant for rotator cuff repairs, and several randomized clinical trials have studied the functional effects and patient outcomes of this treatment, with the goal of increasing healing of the enthesis and reducing pain and inflammation of patients after repair . There are several reviews that summarize patient outcomes and compare data across multiple studies, with few finding significant improvements in patient outcomes and pain levels in patients with PRP‐treated rotator cuff repairs versus control repairs . The majority of studies fail to find significant results, as most clinical studies have shown that PRP has no significant effects on healing, retear rate, pain, or functional outcomes at long‐term follow‐up tests .…”
Section: Biomolecule‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
“…14,15,48 There are several reviews that summarize patient outcomes and compare data across multiple studies, with few finding significant improvements in patient outcomes and pain levels in patients with PRP-treated rotator cuff repairs versus control repairs. 15,49 The majority of studies fail to find significant results, as most clinical studies have shown that PRP has no significant effects on healing, retear rate, pain, or functional outcomes at long-term follow-up tests. 50,51 However, interesting differences have been observed when comparing treatment subgroups.…”
Section: Biomolecule-based Therapies For Rotator Cuff Repairmentioning
confidence: 99%